ATM interaction with GRP94 modulates oncogenic receptor expression and signaling and microglial activation - Paige E. Burrell; Donald E. Fleenor; Olivia M. Nicholson; Changjuan Shao; Michael B. Kastan (Proceedings of the National Academy of Sciences, 2025)
Ataxia-telangiectasia (A-T), caused by biallelic mutations in the ATM gene, leads to multiple disease phenotypes, including cerebellar neurodegeneration, radiosensitivity, cancer predisposition, immunodeficiency, insulin resistance, and pulmonary inflammation. ATM plays a central role in regulating cellular responses to DNA breakage [M. B. Kastan, J. Bartek, Nature 432 , 316–323 (2004)], but several cellular and physiologic abnormalities associated with ATM dysfunction suggest the possibility of noncanonical roles for ATM as well. Herein, we identified the HSP90 paralogue, GRP94, as an ATM interactor/substrate and found that ATM influences N- glycosylation of GRP94 and its subsequent activation/translocation to the plasma membrane, where it serves as a scaffold protein and stabilizer for several membrane proteins, including receptor tyrosine kinases (RTKs), such as EGFR and IGF1-R. In selected cell types, ATM loss/inhibition resulted in increased cell surface expression of RTKs and overactivation of RTK pathways, alterations that were rescued by specific inhibition of cell surface GRP94. This ATM/GRP94 pathway also regulated the activation of microglial cells, manifest as increased cytokine production and phagocytosis activity associated with ATM loss/inhibition and reversal of that activation with GRP94 inhibition. These results identified GRP94 as an ATM interactor and apparent substrate and demonstrated specific critical regulatory roles for ATM outside of DNA damage signaling. These insights provide potential explanations for several of the phenotypes associated with ATM dysfunction and potential opportunities for novel approaches to blunt clinical symptoms in A-T, and also suggest that other neurodegenerative and inflammatory disorders might benefit from selective inhibition of cell surface GRP94.